Inside the biology of early T-cell precursor acute lymphoblastic leukemia: the perfect trick - Francesco Tarantini; Cosimo Cumbo; Luisa Anelli; Antonella Zagaria; Giorgina Specchia; Pellegrino Musto; Francesco Albano (BMC, 2021)
Abstract Early T-cell precursor acute lymphoblastic leukemia (ETP-ALL) is a rare, distinct subtype of T-ALL characterized by genomic instability, a dismal prognosis and refractoriness to standard chemotherapy. Since its first description in 2009, the expanding knowledge of its intricate biology has led to the definition of a stem cell leukemia with a combined lymphoid-myeloid potential: the perfect trick. Several studies in the last decade aimed to better characterize this new disease, but it was recognized as a distinct entity only in 2016. We review current insights into the biology of ETP-ALL and discuss the pathogenesis, genomic features and their impact on the clinical course in the precision medicine era today.